1997
DOI: 10.1128/jvi.71.9.6805-6815.1997
|View full text |Cite
|
Sign up to set email alerts
|

Bovine papillomavirus type 1 DNA replication: the transcriptional activator E2 acts in vitro as a specificity factor

Abstract: We previously devised cell-free conditions supporting efficient replication of bovine papillomavirus type 1 (BPV1) DNA (C. Bonne-Andréa, S. Santucci, and P. Clertant, J. Virol. 69:3201-3205, 1995): the use of highly active preparations of viral initiator protein E1, together with extract from a particular cell source, allowed the synthesis of complete DNA circles through successive rounds of replication; this occurred in the absence of the viral transcriptional activator E2, required in vivo for the replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Binding of E2 to the C-terminal domain of E1 may also affect DNA binding. This is suggested by the observation that in the absence of E2-binding sites, E2 suppresses the binding of E1 to the origin (32) and to nonspecific DNA (6). Together with our results, these findings support the notion that conformational changes in the E1 C-terminal domain, brought about upon binding ATP-Mg, can affect the interaction of E1 with DNA.…”
Section: Figsupporting
confidence: 90%
“…Binding of E2 to the C-terminal domain of E1 may also affect DNA binding. This is suggested by the observation that in the absence of E2-binding sites, E2 suppresses the binding of E1 to the origin (32) and to nonspecific DNA (6). Together with our results, these findings support the notion that conformational changes in the E1 C-terminal domain, brought about upon binding ATP-Mg, can affect the interaction of E1 with DNA.…”
Section: Figsupporting
confidence: 90%
“…E2 enhances replication of the viral DNA through complex formation with the viral E1 protein, which has characteristics of a replication initiator protein (61). In vitro and in vivo studies have demonstrated that binding of E2 to E1 increases the specificity of the origin recognition by E1 (8,20,36,39,43,54,55,63,71). The BPV1 E2 protein was first characterized as an enhancer-binding protein that could stimulate transcription from multimerized E2 binding sites located upstream of heterologous promoters in transient assays (3,27,58).…”
mentioning
confidence: 99%
“…In addition, E2 may prevent nucleosome formation around the ori in vivo (19). By virtue of its strong and specific affinity to the E2 protein binding site and its interaction with the E1 protein, the E2 protein is critical to the initiation of replication from ori (4,6,17,22,31,33,40), but it appears to be dispensable during elongation (20).…”
mentioning
confidence: 99%